2015
DOI: 10.1021/acs.orglett.5b01174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Paclitaxel. 2. Construction of the ABCD Ring and Formal Synthesis

Abstract: A formal synthesis of the antitumor diterpenoid paclitaxel (Taxol) is described. The ABC ring of paclitaxel, synthesized starting from 1,3-cyclohexanedione and tri-O-acetyl-d-glucal by SmI2-mediated cyclization as the key transformation, was successfully converted to Takahashi's tetracyclic oxetane intermediate. A double Chugaev reaction was employed for introduction of the strained bridgehead olefin, and stereoselective formation of the oxetane ring afforded the known synthetic intermediate, completing the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…178 Further synthetic studies directed at paclitaxel continue to be reported. 179 A large number of esters of jatrophanes, lathyranes, myrsinanes, daphnanes, tiglianes and ingenanes have been isolated, particularly from members of the Euphorbiaceae and Thymelaeaceae. Care must be taken in the separation of these compounds to avoid conditions that may lead to acyl migration and transesterication.…”
Section: Macrocyclic Diterpenoids and Their Cyclization Productsmentioning
confidence: 99%
“…178 Further synthetic studies directed at paclitaxel continue to be reported. 179 A large number of esters of jatrophanes, lathyranes, myrsinanes, daphnanes, tiglianes and ingenanes have been isolated, particularly from members of the Euphorbiaceae and Thymelaeaceae. Care must be taken in the separation of these compounds to avoid conditions that may lead to acyl migration and transesterication.…”
Section: Macrocyclic Diterpenoids and Their Cyclization Productsmentioning
confidence: 99%
“…Indeed, Taxol™ ( 1 , Figure 1) can be treated as a barometer to measure progress and advances in the science of chemical synthesis. This iconic natural product has been prepared on ten separate occasions (seven total syntheses 4–12 and three formal syntheses 1316 ), elegantly demonstrating the feasibility of its reconstitution by purely chemical means. Notwithstanding the beauty of these landmark accomplishments, they are 8–9 orders of magnitude less efficient than biological production.…”
mentioning
confidence: 93%
“…Every year brings its bounty. In 2015, chemists published a new and elegant route to the anticancer drug paclitaxel (Taxol) 1 , and syntheses of a nodulisporic acid that might act as an insecticide 2 and, in this journal, of an anti-HIV alkaloid 3 . There are also less utilitarian reasons for making molecules.…”
Section: Why Synthesize?mentioning
confidence: 99%